Do Marginal Firms in Bolivia Benefit from Formalizing? - McKenzie, David (World Bank, Washington, DC, 2012)
The seventh in impact series summarizes research which arose from research staff working together with operational staff on a World Bank Economic and Sector Work (ESW) on policies to increase the formality and productivity of firms in Bolivia. It is also illustrative of how an instrumental variables approach can be informative in impact evaluations.